CELLULOLYTIC BACTERIA OF SOIL OF GUNUNG HALIMUN NATIONAL PARK - I Made Sudiana; Ritai Dwi Rahayu; Hartati Imanuddin; Maman Rahmansyah (BERITA BIOLOGI, 2001)
The population of aerobic cellulolyitic bacteria (ACB) of soil Gunung Halimun National park and its celulolytic capacity were studied.The soil samples were collected from various altitude (500-1500) m asl.Microbial isolation was performed by culture enrichment technique with CMC (carboxymethyl cellulose) as the major carbon sources.The quantitative determination of ACB was performed by growing the microbes on CMC containing media, and utilizing congored as an indicator.ACB was indicated by formation of clearing zone surrounding growing colony.Cellulytic capacity of each isolates was determined by analysing the ratio of colony and clear zone formation.ACB were quite heterogenous include Bacillus sp., Clostridium sp., Chromobacterlum sp., Enterobacter sp., Moraxella sp. and Pseudomonas sp.